Anti-diabetic effects of Bifidobacterium animalis 01 through improving hepatic insulin sensitivity in type 2 diabetic rat model. (April 2020) - Zhang, Jinlan; Wang, Shibo; Zeng, Zhu; Qin, Yuxuan; Shen, Qian; Li, Pinglan
Graphical abstract: Highlights: Type 2 diabetic rats models were induced by HFD and low-dose streptozotocin. The anti-diabetic effects of Bifidobacterium animalis 01 had been investigated. Bifidobacterium animalis 01 ameliorated the T2DM liver injuries. The anti-diabetic mechanisms of Bifidobacterium. animalis 01 were proposed. Abstract: The anti-diabetic effects of Bifidobacterium animalis 01 and its potential mechanisms were investigated. Male SD rats were given a high-fat chow diet with low-dose streptozotocin (30 mg/kg BW) to induce T2DM. The supplements with B. animalis 01 were given in a pre- and post-treatment method. Oral administration of B. animalis 01 decreased food and water intake, blood glucose concentration, and glycosylated hemoglobin level. Treatment with B. animalis 01 improved OGTT, HOMA-IR, lipid profiles, representative cytokines, and liver injury markers in the serum. B. animalis 01 also exhibited hepatoprotective effects by reducing hepatic tissues injuries, increasing the glycogen levels, and improving the antioxidant indexes. Furthermore, B. animalis 01 treatment showed beneficial influence on the gene expressions of hepatic glucose metabolism and IRS/PI3K/AKT pathway. Moreover, B. animalis 01 administration positively regulated hepatic Keap1/Nrf2 pathway. The results suggested that the hepatic protective effect of B. animalis 01 against diabetes attributed to IRS/PI3K/AKT and Keap1/Nrf2 signaling activation.